2018
DOI: 10.1176/appi.ps.201700451
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Peer-Staffed Crisis Respite Program as an Alternative to Hospitalization

Abstract: Peer-staffed crisis respite services resulted in lowered rates of Medicaid-funded hospitalizations and health expenditures for participants compared with a comparison group. The findings suggest that peer-staffed crisis respites can achieve system-level impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 12 publications
2
28
0
10
Order By: Relevance
“…Biopsychosocial treatments including medication management were previously found to increase patient satisfaction [46], as also evidenced in the present brief intervention team. Surveys have found that patients in crisis prefer to be treated in a friendly, homelike environment like that offered in the study crisis center team rather than in ED or hospitals [30,36].…”
Section: Aggressive or Overly Critical Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsychosocial treatments including medication management were previously found to increase patient satisfaction [46], as also evidenced in the present brief intervention team. Surveys have found that patients in crisis prefer to be treated in a friendly, homelike environment like that offered in the study crisis center team rather than in ED or hospitals [30,36].…”
Section: Aggressive or Overly Critical Family Membersmentioning
confidence: 99%
“…The risk of cultural clash between community organization or peer support staff providing services and health care professionals, particularly concerning recognition of professional expertise, was another important issue identified [ 27 29 ]. Training and supervision of peer support staff by health professionals were viewed as key indicators of success [ 30 ]. Regarding individual factors, interpersonal skills were identified as critical [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jedes der eingeschlossenen CR beschreibt eigene Ziele und Werte, worunter sich einige an der Definition der National Coalition for Mental Health Recovery (NCMHR) orientieren, die in den USA die Implementierung von CR vorantreibt [19]. Häufig wird das Ziel benannt, die Inanspruchnahme von psychiatrischen Rettungsstellen und Krankenhäusern und damit verbundene Belastungen, lange Behandlungsverläufe sowie teilweise auch Kosten zu reduzieren [6,10,[20][21][22]. Einige CR sind strukturell in das Versorgungssystem eingebettet.…”
Section: Ziele Werte Und Selbstverständnisunclassified
“…Die angewendeten Aufnahmekriterien variieren z. T. erheblich: Einige CR nehmen nur Personen mit festem Wohnsitz und Krankenversicherung auf [22,23,26]. Andere nutzen als Kriterium bestimmte Diagnosegruppen (Psychose oder Sucht) [4,6]. In vielen Projekten wird das Nichtvorliegen von Eigen-oder Fremdgefährdung vorausgesetzt.…”
Section: Modelle Und Umsetzungsvariantenunclassified
See 1 more Smart Citation